2020
DOI: 10.4049/jimmunol.1900778
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell–Intrinsic Expression of MHC Class II Regulates the Immune Microenvironment and Response to Anti–PD-1 Therapy in Lung Adenocarcinoma

Abstract: MHC class II (MHCII) expression is usually restricted to APC but can be expressed by cancer cells. We examined the effect of cancer cell-specific MHCII (csMHCII) expression in lung adenocarcinoma on T cell recruitment to tumors and response to anti-PD-1 therapy using two orthotopic immunocompetent murine models of non-small cell lung cancer: CMT167 (CMT) and Lewis lung carcinoma (LLC). We previously showed that CMT167 tumors are eradicated by anti-PD1 therapy, whereas LLC tumors are resistant. RNA sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 51 publications
8
84
0
Order By: Relevance
“…Indeed, tumor specific MHC-II expression is associated with superior prognosis and/or improved response to immune checkpoint inhibitor therapy in multiple cancers, as well as enhanced tumor rejection in mouse models 27 , 28 , 59 62 . Recent loss of function and complementation studies in murine carcinoma cells also showed that tumor cell expression of MHC-II is associated with higher Th1 cytokine levels, T-cell infiltration, and sensitivity to anti-PD-1 therapy 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tumor specific MHC-II expression is associated with superior prognosis and/or improved response to immune checkpoint inhibitor therapy in multiple cancers, as well as enhanced tumor rejection in mouse models 27 , 28 , 59 62 . Recent loss of function and complementation studies in murine carcinoma cells also showed that tumor cell expression of MHC-II is associated with higher Th1 cytokine levels, T-cell infiltration, and sensitivity to anti-PD-1 therapy 63 .…”
Section: Discussionmentioning
confidence: 99%
“…An important recent observation was made by Johnson and colleagues concerning the participation of MHC-II expression in anti-PD-1 therapies [ 143 ]. Two orthotopic immunocompetent murine models of non-small cell lung cancer, the cell line CMT167, which is sensitive to anti-PD1 therapy and the Lewis lung carcinoma (LLC), which is resistant, were used.…”
Section: Ciita and Cancermentioning
confidence: 99%
“…Ectopic expression of CIITA in LLC rendered these cells MHC-II-positive and sensitized the tumors to anti-PD-1 therapy. Upregulation of CIITA was also associated with increased T-cell infiltration and a survival benefit in patient-derived lung adenocarcinomas [ 143 ].…”
Section: Ciita and Cancermentioning
confidence: 99%
“…Notably, while both CMT167 and LLC cells show induction of some IFNγ-inducible genes in vivo, including PD-L1, CMT167 cells showed a unique induction of genes encoding the MHC class II antigen presentation and processing pathway. 12 In this study, we aimed to characterize the determinants of divergent IFNγ responsiveness between these tumor lines in vitro in order to gain mechanistic insights that may lead to novel approaches to enhance IFNγ sensitivity and thus make more tumors susceptible to PD-1/ PD-L1 checkpoint blockade, with an emphasis on MHC II regulation. Our studies point to a critical requirement for epigenetic and post-translational-dependent mechanisms that actively restrict IFNγ induction of the MHC class II machinery in NSCLC.…”
mentioning
confidence: 99%